Does coronary calcium score add value to European SCORE in an asymptomatic population?. (14th October 2021) - Temtem, M; Mendonca, M I; Soares, C; Serrao, M; Rodrigues, R; Santos, M; Sousa, J A; Mendonca, F; Sousa, A C; Rodrigues, M; Henriques, E; Freitas, S; et al.
Abstract: Background: Despite being a controversial subject, multiple guidelines mention the use of Coronary Artery Calcification (CAC) scoring in the cardiovascular risk prediction in the asymptomatic population. Adding CAC score to European SCORE (Systematic Coronary Risk Evaluation) may improve the prediction of MACE (Major Adverse Cardiovascular Events), providing better cardiovascular risk stratification. Purpose: Our study aims to evaluate the impact of CAC severity in MACE prediction compared with SCORE and estimate the additional value of CAC score in cardiovascular risk stratification in a low- risk region and asymptomatic population. Methods and results: The study consisted of a prospective registry of 1110 asymptomatic individuals free of known coronary heart disease, enrolled from the GENEMACOR study and referred for computed tomography for the CAC scoring assessment. The mean age was 51.6±8.2 years, and 74.1% were male. This population was followed for a mean of 5.2±3.3 years for the primary endpoint of all-cause of cardiovascular events. The extent of CAC differs significantly between men and women in the same age group. Therefore, the distribution of CAC score by age and gender was done using Hoff's nomogram (a). According to this nomogram, 3 categories were created: low CAC (0≤CAC<100 and P<50); moderate CAC (100≤CAC<400 or P50–75) and high CAC (CAC≥400 or P>75). Through a Cox regression for MACE occurrence, SCORE does not remain in the equation, and the higher severity level of CAC presented a significant risk of MACE occurrence with an HR of 7.943 (95% CI 2.948 – 21.401; p<0.0001). Using the C-index, CAC was superior to SCORE (0.729 vs 0.615; p<0.0001). Adding CAC score to SCORE increased MACE prediction compared to SCORE alone (AUC 0.77 vs 0.615; p=0.003). Conclusion: Our results point to the importance of the CAC score inclusion in primary prevention to improve cardiovascular risk stratification. CAC score in clinical practice could have a prognostic impact on MACE prediction. Larger prospective multicenter cohorts with longer follow-up should reproduce and validate these findings. FUNDunding Acknowledgement: Type of funding sources: None.